1904 N.J. Laws 178 - (:unkn) unknown (My University, 1904)
Ch. 68, 1: Any person trespassing upon any marsh, swamp or meadow grounds lying within the bounds of any meadow bank company, organized or to be organized under the provisions of the act . . . where the owners and possessors of the said marsh, swamp or meadow lands, lying within the bounds of such meadow bank company, have caused or permitted or suffered, or shall hereafter cause or permit or suffer the same to be subjected to the overflowing of the tide, carrying a gun, after public notice on the part of the owner, possessor, lessee or licensee of any such marsh, swamp or meadow grounds subjected to the overflowing of the tide, forbidding such trespassing, such notice being posted conspicuously adjacent to the highway binding on such lands or adjacent to any usual entrance-way to said land, shall be deemed and adjudged to be a disorderly person.
Keywords: CARRY